2019
DOI: 10.1177/0269881119856558
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic potential and underlying mechanism of sarcosine (N-methylglycine) in N-methyl-D-aspartate (NMDA) receptor hypofunction models of schizophrenia

Abstract: Background: Compelling animal and clinical studies support the N-methyl-D-aspartate receptor (NMDAR) hypofunction hypothesis of schizophrenia and suggest promising pharmacological agents to ameliorate negative and cognitive symptoms of schizophrenia, including sarcosine, a glycine transporter-1 inhibitor. Aims and methods: It is imperative to evaluate the therapeutic potential of sarcosine in animal models, which provide indispensable tools for testing drug effects in detail and elucidating the underlying mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 73 publications
(95 reference statements)
2
14
0
Order By: Relevance
“…However, the subanalgesic doses of each inhibitor failed to produce significant increase in glycine content in the CSF, but a tendency of this increase was noticed. Data on increase in the glycine level in CSF upon treatments of rodents with selective GlyT-1 or GlyT-2 inhibitors have been published by other research groups [28][29][30]. However, to the best of our knowledge, there are no data available on the effects of the GlyT-1 and GlyT-2 inhibitors' combination on the pain evoked by nerve damage or on the glycine level in the CSF.…”
Section: Discussionmentioning
confidence: 99%
“…However, the subanalgesic doses of each inhibitor failed to produce significant increase in glycine content in the CSF, but a tendency of this increase was noticed. Data on increase in the glycine level in CSF upon treatments of rodents with selective GlyT-1 or GlyT-2 inhibitors have been published by other research groups [28][29][30]. However, to the best of our knowledge, there are no data available on the effects of the GlyT-1 and GlyT-2 inhibitors' combination on the pain evoked by nerve damage or on the glycine level in the CSF.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, although recent studies report that SR and DAO are not solely expressed in astrocytes [100][101][102], astrocytes play a vital role in the secretion of D-serine and the regulation of NMDAR function [96,103]. Several animal studies with constitutive deletion of SR in SR -/mutant mice indicated that these mice had long-term D-serine deficiency, neurobiological abnormalities, spatial and fear memory deficits, sociality problems, and hyperlocomotion activity [104][105][106][107][108]. Intriguingly, a recent study further indicated that SR -/mutant mice exhibited a reduction in the freezing response in the trace fear conditioning task and hyperlocomotion in the open-field task, which were normalized by a single administration of sarcosine (an astrocytic glycine transporter-1 inhibitor) [108].…”
Section: Using Animal Models To Investigate Astrocytic Regulation Of Glutamate Transmission In Schizophreniamentioning
confidence: 99%
“…Several animal studies with constitutive deletion of SR in SR -/mutant mice indicated that these mice had long-term D-serine deficiency, neurobiological abnormalities, spatial and fear memory deficits, sociality problems, and hyperlocomotion activity [104][105][106][107][108]. Intriguingly, a recent study further indicated that SR -/mutant mice exhibited a reduction in the freezing response in the trace fear conditioning task and hyperlocomotion in the open-field task, which were normalized by a single administration of sarcosine (an astrocytic glycine transporter-1 inhibitor) [108]. However, little is known about NMDAR hypofunction induced by DAO overexpression in animal models.…”
Section: Using Animal Models To Investigate Astrocytic Regulation Of Glutamate Transmission In Schizophreniamentioning
confidence: 99%
See 2 more Smart Citations